Analisis Value Stream Mapping (VSM) untuk Mengeliminasi Pemborosan pada Produksi Plywood - Soleh, Muhamad; Kurniawan, Aditya; Warso, Warso; Khamdani, Haris (UM Purwokerto Press, 2023)
This research aims to improve the identification of issues in plywood production at CV. Karya Purabaya. The inefficient production process leads to production times not meeting the standards, causing the company to often fail to fulfill orders on time. To implement improvements, the company needs to examine the production system comprehensively to pinpoint the issues in the production process. Value Stream Mapping (VSM) analysis, which is one of the Lean Manufacturing methods, is used to identify wasteful practices in the plywood production system. In identifying wasteful practices, Value Stream Analysis Tools (VALSAT) is utilized to identify connections and relationships between different wasteful practices. Waste Assessment Questionnaire (WAQ) is used to identify the most dominant waste, and Fishbone Diagram is employed to determine the root causes of the waste. Based on the results from the WAQ calculations, it was found that the most dominant waste is Overproduction with a percentage of 22.43%, followed by Inventory with a percentage of 20.40%. Furthermore, the WRM calculations reveal that inappropriate processing has a high percentage of 20.3%, and the value to Inventory has the highest percentage of 21.0%. The proposed improvements to minimize the most dominant waste at CV. Karya Purabaya include balancing the production process flow by implementing line balancing with an efficiency rate of 73,85%, conducting regular machine maintenance, making accurate planning and forecasting, and reducing defect.